Light-Mediated Growth of Noble Metal Nanostructures (Au, Ag, Cu, Pt, Pd, Ru, Ir, Rh) From Micro- and Nanoscale ZnO Tetrapodal Backbones - Demille, Trevor B.; Hughes, Robert A.; Preston, Arin S.; Adelung, Rainer; Mishra, Yogendra Kumar; Neretina, Svetlana (Frontiers in Chemistry, 2018)
Micro- and nanoscale ZnO tetrapods provide an attractive support for metallic nanostructures since they can be inexpensively produced using the flame transport method and nanoparticle synthesis schemes can take advantage of a coupled response facilitated by the formation of a semiconductor-metal interface. Here, we present a light-mediated solution-based growth mode capable of decorating the surface of ZnO tetrapods with nanostructures of gold, silver, copper, platinum, palladium, ruthenium, iridium, and rhodium. It involves two coupled reactions that are driven by the optical excitation of electron-hole pairs in the ZnO semiconductor by ultraviolet photons where the excited electrons are used to reduce aqueous metal ions onto the ZnO tetrapod as excited holes are scavenged from the surface. For the most part, the growth mode gives rise to nanoparticles with a roundish morphology that are uniformly distributed on the tetrapod surface. More sophisticated geometries are, however, obtained for syntheses utilizing aqueous metal nitrates as opposed to chlorides, a result that suggests that the anion plays a role in shape determination. It is also demonstrated that changes to the molarity of the metal ion can influence the nanostructure nucleation rate. The catalytic activity of tetrapods decorated with each of the eight metals is assessed using the reduction of 4-nitrophenol by borohydride as a model reaction where it is shown that those decorated with Pd, Ag, and Rh are the most active.